Case of cytomegalovirus colitis in an immunocompetent patient: a rare cause of abdominal pain and diarrhea in the elderly - Harano, Yumi (Int J Gen Med, 2015)
Cytomegalovirus (CMV) colitis usually occurs in immunocompromised patients after undergoing organ transplantation or chemotherapy. We report the case of a 60-year-old immunocompetent Japanese woman who presented with abdominal pain and bloody diarrhea. She was initially diagnosed as having ischemic colitis with pseudomembranous colitis on the basis of her symptoms, Clostridium difficile antigen positivity, and colonoscopic findings, which showed ulcer formation from the sigmoid colon to rectum. In spite of bowel rest and administration of metronidazole, her symptoms did not improve. On follow-up colonoscopy, ulcerations remained unchanged. Biopsy of the ulceration revealed CMV-infected cells leading to a diagnosis of CMV colitis. CMV colitis is a rare but possible differential diagnosis in immunocompetent patients. We recommend endoscopic biopsy in a case of refractory abdominal pain and bloody diarrhea.